A global invasion by the thrip, Frankliniella occidentalis: Current virus vector status and its management. (23rd October 2019) - He, Zhen; Guo, Jing‐Fei; Reitz, Stuart R.; Lei, Zhong‐Ren; Wu, Sheng‐Yong
Abstract: Western flower thrip, Frankliniella occidentalis (Pergande), is among the most economically important agricultural pests globally, attacking a wide range of vegetable and horticultural crops. In addition to causing extensive crop damage, the species is notorious for vectoring destructive plant viruses, mainly belonging to the genera Orthotospovirus, Ilarvirus, Alphacarmovirus and Machlomovirus . Once infected by orthotospoviruses, thrips can remain virulent throughout their lifespan and continue transmitting viruses to host plants when and wherever they feed. These irruptive viral outbreaks in crops will permanently disrupt functional integrated pest management systems, and typically require a remedial treatment involving insecticides, contributing to further development of insecticide resistance. To mitigate against this continuing cycle, the most effective management is early and comprehensive surveillance of the pest species and recognition of plant viruses in the field. This review provides information on the pest status of F. occidentalis, discusses the current global status of the viruses vectored by this thrip species, examines the mechanisms involved in transmitting virus‐induced diseases by thrips, and reviews different management strategies, highlighting the potential management tactics developed for various cropping systems. The early surveillance and the utilization of potential methods for control of both F. occidentalis and viruses are proposed.